THE IMPLEMENTATION OF A SCALE SYSTEM IN THE SELLING OF BROILER CHICKEN IN THE DAYA MARKET REVIEWED FROM ISLAMIC ECONOMIC ASPECTS - Ambo Dalle Bohari; Syarifuddin Syarifuddin; Isra Ananda Sari (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2020)
This study aims to determine the measurements and scales used by broiler chicken sellers in accordance with the concept of Islamic economics in the Makassar Daya market. The data analysis method used in the research is qualitative analysis. Data collection techniques such as observation, documentation, direct interviews with relevant parties. The results of this study indicate that the application of scales in the sale and purchase of broiler chicken traders in Makassar Daya Market is not in accordance with the main principles of Islamic economics, namely promoting an honest and trustworthy attitude. This discrepancy is caused by several things, namely from the scales used that are already improper, for example, the scales that are not functioning normally, or experiencing other damage, apart from that this discrepancy is also caused by the behavior of the rice seller himself who is deliberately doing a mismatch of scales because he wants to get more profile. This is also supported by the lack of attention from the government or religious institutions that offend or elevate Islamic business ethics into a system that will have a positive impact on the business they run.